Perbedaan Kemampuan Berpikir Spasial Siswa berdasarkan Gender di SMA Muhammadiyah 1 Karanganyar - At tamimi, Ghulam Abas; Wardhani, Puspita Indra; Dewi, Ratih Puspita; Widiyatmoko, Wahyu; Wibowo, Yunus Aris (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Spatial thinking ability in the 21st century is crucial for students to respond to challenges and global competition While each student possesses different spatial thinking abilities these abilities are also vulnerable to decline due to the uncertain global conditions This study aims to analyze spatial thinking abilities based on students gender through the Spatial Thinking Ability Test STAT The research employs a comparative method with quantitative data analysis using a two sample t test The subjects of this study were male and female students at Muhammadiyah Senior High School 1 Karanganyar Data collection was carried out using a test The results showed that the average spatial thinking ability score for male students was 181 45 while female students scored 139 10 The Asymp Sig 2 tailed value of 0 000 with a significance value sig lt; 0 05 indicates that the alternative hypothesis Ha is accepted while the null hypothesis H0 is rejected In conclusion there is a significant difference in spatial thinking abilities suggesting that male students at Muhammadiyah Senior High School 1 Karanganyar tend to have higher spatial thinking abilities than female students < em>< p>